Light assisted synthesis of poly-para-phenylene on Ag(001). (15th November 2021) - Langlais, V; Schneider, K; Tang, H
Abstract: A detailed study of poly-para-phenylene (PPP) obtained by light-assisted on-surface-synthesis (OSS) on Ag(100) was carried out by scanning tunneling microscopy and spectroscopy together with density functional theory calculations. The use of light in combination with heat allows to lower by 50 K annealing temperature the each stage of the Ullmann coupling. Debromination of the 4, 4″ dibromo-p-terphenyl precursors was thus realized at 300 K, the formation of the first oligomers from the organometallic intermediate by silver bridging atom release at 423 K and PPP by complete elimination of the silver at 473 K. This approach to lower the reaction temperature permits to enhance the Ag(100) surface reactivity to become comparable to that of Cu(111). The underlying mechanism of light effect was proposed to occur via surface mediated excitation, with the creation of photoexcited electrons known as hot electrons correlated with surface plasmon excitation. This original pathway combining both light and heat provides an additional parameter to control OSS by separating the precursor activation stage from the diffusion.